Pengaruh EWOM, Citra Merek, dan Kemudahan Penggunaan Terhadap Keputusan Pembelian Produk Skincare pada Tokopedia - Fatma Yani; Tiurniari Purba (Jurnal Riset Rumpun Ilmu Ekonomi, 2026)
This study aimed to uncover the extent to which eWOM, perceived brand image, and platform ease of use influence consumer purchasing decisions for Skintific moisturizer on Tokopedia. The method employed was descriptive quantitative, selecting a sample of 96 consumers who had purchased Skintific products, using a purposive sampling technique based on the Lemeshow formula to ensure representativeness. Data were collected through a questionnaire and then analyzed using a series of tests including validity, reliability, classical assumption checking, multiple linear regression, and hypothesis testing using t- and F-tests. The analysis showed that eWOM contributed 13.9% to purchasing decisions, brand image 23.4%, and ease of use 46.1%. The coefficient of determination (R²) of 75.4% indicates that these variables collectively explain most of the variation in purchasing decisions. The t- and F-tests confirmed a positive and significant influence, both individually and simultaneously, on consumer purchasing behavior on Tokopedia.